A study of converter configurations for vehicular applications - Gupta, Ankur Kumar; Mitra, Uliya; Verma, Hemant Kumar (Trends in Computer Science and Information Technology, 2024)
Renewable energy sources like hydro, wind, geothermal and solar along with fuel cells are nowadays solutions to the global energy crisis, environmental issues, and fossil fuel exploitation. The nature of the output of these renewable sources is D.C. The role of DC-DC converters in the integration of energy sources with microgrids is vital. These converters find their major applications in power generation, energy systems, vehicular applications, portable electronic devices, aerospace, etc. These converters help to boost the voltage and improve the reliability, stability, efficiency, and performance of the system. This study gives a brief overview of three DC-DC converters of non-isolated topology. They are: Clamped H-type boost DC-DC converter, Multi-Port Dual-Active-Bridge DC-DC Converter, and Four-Phase Interleaved Four-Switch Buck-Boost Converter. This study will make researchers learn and make their concept clear about the operation, performance, and usage of these converters.